2022
DOI: 10.1021/jacs.2c01094
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Spillover-Bridged Volmer/Tafel Processes Enabling Ampere-Level Current Density Alkaline Hydrogen Evolution Reaction under Low Overpotential

Abstract: Water-alkaline electrolysis holds a great promise for industry-scale hydrogen production but is hindered by the lack of enabling hydrogen evolution reaction electrocatalysts to operate at ampere-level current densities under low overpotentials. Here, we report the use of hydrogen spillover-bridged water dissociation/ hydrogen formation processes occurring at the synergistically hybridized Ni 3 S 2 /Cr 2 S 3 sites to incapacitate the inhibition effect of high-current-density-induced high hydrogen coverage at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
100
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(117 citation statements)
references
References 63 publications
3
100
0
Order By: Relevance
“…The free energies reflecting the adsorption ability OH* and H* species on the active sites were calculated. It was found that the adsorbed OH*species can be easily removed from the corner site to form an OH - anion (0.31 eV), which fits well with the widely accepted one-electron reductive desorption mechanism (OH* + e − → OH − ) 74 76 . While the generated hydrogen atoms (H*) are strongly bound to the corner sites with large free-energies of 0.82 and 0.86 eV for Heyrovsky step (H* + H 2 O + e − →H 2 * + OH − ) and Tafel step (2H* → H 2 *), respectively, which inhibit the formation of hydrogen molecule (H 2 ).…”
Section: Resultssupporting
confidence: 79%
“…The free energies reflecting the adsorption ability OH* and H* species on the active sites were calculated. It was found that the adsorbed OH*species can be easily removed from the corner site to form an OH - anion (0.31 eV), which fits well with the widely accepted one-electron reductive desorption mechanism (OH* + e − → OH − ) 74 76 . While the generated hydrogen atoms (H*) are strongly bound to the corner sites with large free-energies of 0.82 and 0.86 eV for Heyrovsky step (H* + H 2 O + e − →H 2 * + OH − ) and Tafel step (2H* → H 2 *), respectively, which inhibit the formation of hydrogen molecule (H 2 ).…”
Section: Resultssupporting
confidence: 79%
“…Therefore, various Ni 3 S 2 -based heterostructures have been developed for the electrocatalytic hydrogen evolution reaction. 8,[28][29][30][31][32][33] Feng et al designed Cu nanodot-decorated Ni 3 S 2 nanotubes supported on carbon fibers as efficient electrocatalysts for the HER in alkaline media. The strong synergistic effect between Cu nanodots and Ni 3 S 2 nanotubes endows the hybrid electrocatalyst with excellent HER catalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…2,10 In this case, the formed *H has to be transferred from the TM phase to the Pt phase in the rst place, followed by the hydrogen combination and desorption on Pt sites. [11][12][13] In this regard, hydrogen spillover is a recent focus that offers new insights to enhance the *H supply and HER activity of binary catalysts. 12,[14][15][16][17] Hydrogen spillover typically proceeds through hydrogen migration from H-enriched sites (strong *H adsorption sites) to H-decient sites (weak *H adsorption sites), similar to the case of the abovementioned binary system.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] In this regard, hydrogen spillover is a recent focus that offers new insights to enhance the *H supply and HER activity of binary catalysts. 12,[14][15][16][17] Hydrogen spillover typically proceeds through hydrogen migration from H-enriched sites (strong *H adsorption sites) to H-decient sites (weak *H adsorption sites), similar to the case of the abovementioned binary system. 15,18 Interestingly, due to the moderate DG H on Pt sites close to the thermoneutral point, Pt atoms can act as *H donating sites or accepting sites depending on the *H binding strength of the secondary component.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation